Analogs of the hepatocyte growth factor and macrophage-stimulating protein hinge regions act as Met and Ron dual inhibitors in pancreatic cancer cells. Issue 8 (September 2016) - Church, Kevin J.; Vanderwerff, Brett R.; Riggers, Rachelle R.; McMicheal, Michelle D.; Mateo-Victoriano, Beatriz; Sukumar, Sudharsan R.; Harding, Joseph W.
Abstract : Pancreatic cancer is among the leading causes of cancer death in the USA, with limited effective treatment options. A major contributor toward the formation and persistence of pancreatic cancer is the dysregulation of the hepatocyte growth factor (HGF)/Met (HGF receptor) and the macrophage-stimulating protein (MSP)/Ron (MSP receptor) systems. These systems normally mediate a variety of cellular behaviors including proliferation, survival, and migration, but are often overactivated in pancreatic cancer and contribute toward cancer progression. Previous studies have shown that HGF must dimerize to activate Met. Small-molecule antagonists with homology to a 'hinge' region within the putative dimerization domain of HGF have been developed that bind to HGF and block dimerization, therefore inhibiting Met signaling. Because of the structural and sequence homology between MSP and HGF, we hypothesized that the inhibition of HGF by the hinge analogs may extend to MSP. The primary aim of this 'proof-of-concept' study was to determine whether hinge analogs could inhibit cellular responses to both HGF and MSP in pancreatic cancer cells. Our results showed that these compounds inhibited HGF and MSP activity. Hinge analog treatment resulted in decreased Met and Ron activation, and suppressed malignant cell behaviors including proliferation, migration, and invasion in pancreatic cancer cells in vitro . These results suggest that the hinge analogs represent a novel group of molecules that may offer a therapeutic approach for the treatment of pancreatic cancer and warrant further development and optimization. Abstract : Supplemental Digital Content is available in the text.